The origins of dogs: archaeozoology, genetics, and ancient DNA - Verginelli, F; Capelli, C; Coia, V; Musiani, M; Falchetti, M; Ottini, L; Palmirotta, R; Tagliacozzo, A; Mazzorin, I; Mariani-Costantini, R (2006)
The domestication of the dog from the wolf was a key step in the pathway that led to the Neolithic revolution. The earliest fossil dogs, dated to the end of the last glacial period (17,000 to 12,000 years ago), have been found in Russia, Germany and the Middle East. No dogs are represented in the naturalistic art of the European Upper Palaeolithic, suggesting that dogs were introduced at a later date. Genetic studies of extant dog and wolf mitochondrial DNA sequences were interpreted in favour of multiple dog founding events as early as 135-76,000 years ago, or of a single origin in East Asia, 40,000 or 15,000 years ago. Our study included mitochondrial DNA sequences from Italian fossil bones attributed to three Late Pleistocene-Early Holocene wolves (dated from a15,000 to a10,000 14C years ago) and two dogs, dated to a4000 and a3000 14C years ago respectively. Taking paleogeography into account, our phylogenetic data point to a contribution of European wolves to the three major dog clades, in agreement with archaeozoological data. Our phylogeographic studies also suggest genetic differentiation of dogs and wolves related to isolation by geographic distance, supporting multicentric origins of dogs from wolves throughout their vast range of sympatry.